2004
DOI: 10.1038/sj.sc.3101611
|View full text |Cite
|
Sign up to set email alerts
|

A new test to improve the training quality of wheelchair racing athletes

Abstract: Study design: Validation of a new wheelchair racing test. Objective: To assess the reproducibility of test parameters at different, subjectively chosen, intensity levels in wheelchair racing athletes. Setting: Swiss Paraplegic Centre, Nottwil, Switzerland. Subjects: We tested 11 (eight male, three female) young competitive wheelchair racing athletes. Their age was 20.576.4 years, height 164.7716.3 cm and weight 54.179.2 kg. Average weekly training time was 6.872.7 h. All had been engaged in regular training fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…8,9 The ratings of perceived exertion have previously been employed for the prescription and self-regulation of exercise intensity across a range of exercise modalities, including treadmill exercise, cycling, arm-cranking, handcycling and wheelchair propulsion. [10][11][12][13][14] Muller et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The ratings of perceived exertion have previously been employed for the prescription and self-regulation of exercise intensity across a range of exercise modalities, including treadmill exercise, cycling, arm-cranking, handcycling and wheelchair propulsion. [10][11][12][13][14] Muller et al…”
Section: Discussionmentioning
confidence: 99%
“…16 It is recognised that the reliability of exercise intensity is improved with mode-specific familiarisation during low and moderate-intensity, selfregulated exercise guided by the overall RPE. 12,14 However, the prescription and selfregulation of exercise may be enhanced in novice wheelchair users by using an RPE specific to the peripheral exertional signals experienced during hand-rim propulsion.…”
Section: Abstract: Exercise Prescriptionmentioning
confidence: 99%
“…Third, there is no evidence of measures other than overall RPE 6‐20 specifically assessing the test‐retest reliability of an aerobic exercise bout in accordance with appropriate designs (Table 1). Although reliability studies were identified for other subjective intensity measures [40,62], these did not use a study design eligible for evaluating subjective intensity during aerobic exercise (Table 1). For example, acceptable test‐retest reliability has been found in an adequately powered study regarding the intensity classification chart of the PARA‐SCI [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, because the PARA‐SCI is a self‐report measure of overall PA and leisure‐time PA [40], the test‐retest protocol for the intensity classification chart involved recalling the intensity of activities, rather than reporting the intensities of aerobic exercise bouts as they occurred. Another study indicated acceptable reliability for a subjective measure to assess wheelchair racing intensity, but it was ineligible for this review because more than 50% of participants had disabilities other than SCI [62]. Finally, quality could be improved by applying standard reporting criteria based on Table 1 and the COSMIN checklist (Supplement 2); examples would be improved reporting of statistical methods, how missing data were handled, and provision of individual data to allow additional analyses by others, if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been shown that from the first existence of an endurance event, it takes about one decade for elite able-bodied athletes to reach a more stable level of performance 25. There is no doubt that improvement in wheelchair technology and training methods during the 1980s and 1990s have contributed to the decrease in wheelchair marathon times since 1983 1015,26. Racing strategies such as drafting techniques (ie, cycling directly behind a competitor) may also help to improve performance 27…”
Section: Discussionmentioning
confidence: 99%